Application of Indocyanine Green Videoangiography in Aneurysm Surgery: Evidence, Techniques, Practical Tips - Norat, Pedro; Soldozy, Sauson; Elsarrag, Mazin; Sokolowski, Jennifer; Yaǧmurlu, Kaan; Park, Min S.; Tvrdik, Petr; Kalani, M. Yashar S. (Frontiers in Surgery, 2019)
Establishing blood vessel patency in neurovascular surgery is an essential component in treating cerebrovascular disorders. Given the difficulty in confirming complete obliteration of the aneurysm sac, ICG videoangiography has emerged as an intraoperative tool that provides neurosurgeons immediate feedback on the status of vessel flow, allowing for surgical modifications to be made without delay. ICG initially emerged as a tool for assessing hepatic, cardiac, and retinovascular function. It is an inert compound with a high affinity for plasma proteins and fluorescence properties making it the ideal candidate for assessment of vessel patency in neurovascular procedures. Requiring only a bolus peripheral vein injection and integration of a near-infrared imaging device into the surgical microscope, ICG can be visualized without disrupting operating room workflow or the surgical field. Quick response time, high-spatial resolution, and low complication rates are features of ICG videoangiography that prove advantageous when compared to the gold standard intra- and postoperative digital subtraction angiography (DSA). Despite this, ICG is not without limitations, specifically in the setting of atherosclerotic vessels, giant, and complex aneurysms. Additionally, there are instances where DSA may prove superior in detecting vessel stenosis and outflow obstruction, prompting the recommendation of ICG as an adjunct to, rather than complete replacement of DSA. In this article, the authors provide a brief overview of the biochemical properties and historical origins of ICG viedoangiography in addition to discussing its current application in aneurysm surgery.